2016
DOI: 10.17344/acsi.2015.2109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structures, molecular docking, and urease inhibitory activity of transition metal complexes with 2-[4-(4-fluorophenyl)piperazin-1-yl]acetic acid

Abstract: Two novel mononuclear complexes,2) (HL = 2-[4-(4-fluorophenyl)piperazin-1-yl]acetic acid) were synthesized and structurally determined by single-crystal X-ray diffraction. Their inhibitory activities were tested in vitro against jack bean urease. Molecular docking was investigated to determine the probable binding mode. The experimental values and docking simulation exhibited that complex 1 had better inhibitory activity than the positive reference acetohydroxamic acid (AHA), showing IC 50 value of 0.15 ± 0.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, a very few copper carboxylates have been reported so far with alpha glucosidase, acetylcholine and butyrylcholine esterases inhibition activity. [22][23][24][25] Since enzyme targeting is potential therapy in modern era of medicinal research therefore combining an essential metal and two different organic ligands together in a single molecule to develop lifesaving drugs could be attractive solution. Organic ligands in these complexes affect and regulate their activity by neutralizing the charge on copper ion and facilitating the transport across the cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a very few copper carboxylates have been reported so far with alpha glucosidase, acetylcholine and butyrylcholine esterases inhibition activity. [22][23][24][25] Since enzyme targeting is potential therapy in modern era of medicinal research therefore combining an essential metal and two different organic ligands together in a single molecule to develop lifesaving drugs could be attractive solution. Organic ligands in these complexes affect and regulate their activity by neutralizing the charge on copper ion and facilitating the transport across the cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that copper ion and nickel ion as salt showed the IC 50 value of 1.71 ± 0.56 μM and 8.01 ± 1.21 μM compared to acetohydroxamic acid (AHA, IC50 = 26.99 ± 1.43 μM); however, 2-[4-(4-fluorophenyl) pi-perazin-1-yl] acetic acid (HL) showed no urease inhibitory activities. Zhi-Jian Chen et al reported the urease inhibitory activity of HL as weaker than those of organic compounds synthesized by Sheng et al(Chen et al, 2016;. It appears that electronic configurations, ligand substituents, and the nature of the center of metal influenced the X a) The experimental heats (▵) at 300 K, for (JUB+ KPF).…”
mentioning
confidence: 99%